First measurement of time-dependent CP violation in B0 → K+K- decays - Aaij, R; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; Alkhazov, G; Cartelle, P; et al. (2013)
Direct and mixing-induced CP-violating asymmetries in B0 s → K+K- decays are measured for the first time using a data sample of pp collisions, corresponding to an integrated luminosity of 1.0 fb-1, collected with the LHCb detector at a centre-of-mass energy of 7TeV. The results are CKK = 0.14 ± 0.11 ± 0.03 and SKK = 0.30 ± 0.12 ± 0.04, where the first uncertainties are statistical and the second systematic. The corresponding quantities are also determined for B0→π +π- decays to be Cππ = -0.38±0.15±0.02 and Sππ = -0.71±0. 13±0.02, in good agreement with existing measurements.